Comparison of Trace Elements in High-Molecular-Mass Multiprotein Complex and in Female Milk from Which It Was Obtained - Svetlana E. Soboleva; Natalia P. Zaksas; Georgy A. Nevinsky (The Scientific World Journal)
Background. Many biological processes are performed by different protein complexes. During the association of proteins and enzymes forming specific complexes, the latter can include ions of various metal ions, which may be important for their formation and biological function. Objective of the Studies. However, to date in the literature there are no data on metal ions that are part of any protein complexes. Methods. A very stable multiprotein complex (~1000±100 kDa) was separated from other proteins of nine samples of female milk by gel filtration on Sepharose 4B. The content of microelements in the stable multiprotein complex and milk was analyzed using two-jet plasma atomic emission spectrometry. Results. The content of different elements in milk on average decreased in the order: Ca>P>Mg>Al≥Zn≥Fe>Cu >B (0.76–3500 μg/g of dry milk powder), while the content of some elements was very low (Sr>Mn>Cr>Ba>Pb>Ag>Ni>Cd, <0.03–0.5 μg/g). The content of eight elements in stable multiprotein complex was 1.2-9.6-fold higher than in milk and increased in the order: Ca≈Mg<P<Al<Fe<Pb<Ba<Cr<Cd<Zn, while content of SPC eight metals was 12.3-110-fold higher: Cu (12.3)>B (19.7)>Ag (28.7)>Ni (38)≥Sr (110). Conclusions. The analysis of the relative content of sixteen elements in human milk and oligomeric complexes of proteins was performed for the first time. Data on the content of metals indicate that during the formation of protein which associates the increase in the content of metal ions bound with proteins of the complex can occur. Such metal ions can be important for the formation and biological function of protein complexes.